Un habitat du haut Moyen Âge à “ Foujouin ” (Vernou-sur-Brenne, Indre-et-Loire) - Vincent Hirn; Matthieu Gaultier; Céline Aunay; Chloé Genies; Claire Gerbaud; Philippe Husi; Florian Sarreste (Revue Archéologique du Centre de la France)
The excavations at the bottom of the hillside of the locality of “Foujouin” revealed a small settlement area of the early Middle Ages. The farm plots, buildings, burials and two areas of storage are settled along a trackway.. Set apart a forge, the rest of buildings are living houses associated with agricultural appendices. The activities highlighted within the settlement are not very diversified. A forge of small dimensions was discovered. We were also able to highlight farming activities : agriculture and breeding : cattle, pigs, sheeps and goats; cultivation and storage of crops (cereals and vegetables) which was stored in battery silos or in granaries. This rural settlement presents a continuous activity until the end of its occupation. No anterior settlement was detected in the area explored.